UPLC-MS/MS and Dushman reaction based spectrophotometric method for determination of Ceftazidime, an antibiotic, in medicinal formulation - SIDDIQUI,Masoom Raza (2021)
ABSTRACT: Two analytical methods were developed, one utilizing sensitive UPLC-MS/MS method while other being the spectrophotometric method exploiting the Dushman reaction. Both methods were validated based on ICH guidelines and were successfully applied to quantitate the drug in marketed formulation. UPLC-MS/MS method responded linearly in the range of 1.6 µgmL-1-6.4 µgmL-1 while spectrophotometric procedure followed the Beer’s law in the concentration range of 30-100 µgmL-1. UPLC-MS/MS has been found to have a limit of quantitation of 0.97 µgmL-1 while spectrophotometric method was found to quantitate 14.00 µgmL-1 correctly with high precision. Both the methods showed an excellent recovery of 99.36%-100.91% (% RSD 1.05-1.73) and 98.64%-99.73% (%RSD 0.67-1.68) for UPLC-MS/MS and spectrophotometric, respectively.